FROM THE INDUSTRIAL REVOLUTION TO THE DIGITAL AGE: CONTRIBUTIONS OF LIFE PROJECTS FROM INTEGRATIVE AND TRANSVERSAL PERSPECTIVES - Gauer, Judite Inês Schreiner; Cerutti, Elisabete (Seven Editora, 2025)
The Industrial Revolution was one of the most significant and transformative events in human history, and its importance lies in the fact that it fundamentally altered the way societies produce, live, organize themselves, and relate to the world. The Digital Revolution, on the other hand, is a driving force in 21st-century society, which includes the emergence of disruptive technologies. While the former mechanized the production of goods, the latter is automating and digitizing information, communication, and knowledge, which profoundly impacts the lives of students seeking their place in a constantly transforming job market. It is in this context that this study, based on a literature review, seeks to observe how the changes that have occurred from the Industrial Revolution to the Digital Revolution can be addressed in the Life Project from an integrative and transversal perspective, based on the construction of three reflective axes: (i) observing the paths taken from the Industrial Revolution to digital disruption; (ii) reflecting on how the Life Project can contribute to the subjectivity of students in light of an integrative and transversal approach; (iii) To work, using frameworks, on the theme of Industrial Revolutions, technological innovations and their impacts on society and education. Authors such as Bauman (2001), Delors (2003), Luger (2013), Santaella (2003), among others, discuss the proposed themes from different perspectives. It is concluded that the Life Project is the ideal space to address concepts involving the students’ professional future, helping them to identify their natural aptitudes and passions, which are the basis for lasting and satisfying professional choices. DOI: https://doi.org/10.56238/sevened2025.036-081